Childhood Rheumatic Diseases and COVID-19 Pandemic: An Intriguing Linkage and a New Horizon - Haşlak, Fatih (Balkan Med J, 2020)
As it is known, we are all in a pandemic situation due to a novel coronavirus, officially named “Severe Acute Respiratory Syndrome Coronavirus 2” and the disease caused by the virus named “Coronavirus disease-2019”. The virus seems to has propensity to infect older male individuals with underlying disease. The clinical features were on a large scale that varies from being an asymptomatic carrier to acute respiratory distress syndrome and multiorgan dysfunction. Fever, dry cough and fatigue are the most common symptoms. Not only, the disease seems to be rare and have a milder course in pediatric age but also respiratory failure, multiorgan dysfunction, and death are extremely rare. Although several comorbidities such as hypertension, diabetes and cardiovascular diseases are defined as a risk factor for developing the acute respiratory syndrome and need for intensive care; immune-compromised situations such as rheumatic disease which require immunosuppressive treatment strikingly are not found to be a risk factor for more severe disease course. However, there is a lack of data regarding the effects of “Coronavirus disease-2019” on pediatric patients with rheumatic diseases. Additionally, there are three controversial circumstances that patients with rheumatic diseases are believed to be more likely to have viral infections like “Severe Acute Respiratory Syndrome Coronavirus 2”, on the other hand, antirheumatic drugs may have a protective and therapeutic role in Coronavirus disease-2019 and children are more unlikely to have serious disease course. Therefore, we aimed to have a contributor role for explaining this conundrum and present a bird’s eye view regarding this equivocal issue in this review.